(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India’s historic approval of the GST marked a benchmark in the development of the economy of the country but impact of GST on Indian economy may disrupt the economy for a short-term. Till now, an introduction of VAT (Value Added Tax) at the state level and CENVAT at central level are considered to be largest indirect tax reforms in the country and GST is the next logical step towards making India a unified market. The GST is arguably one of India’s most significant and ambitious reforms ever attempted. Hence, the impact of GST on Indian Economy is going to be very significant. However, determining the exact economic effect hinges on the GST Rates. The macroeconomic impact of GST is significant in terms of growth effects, price effects, current account effects and the effect on the budget balance. It is preferred every economy must adopt GST or VAT at national level to make their economy attractive for foreign investors. By implementing GST, the developing economy like India can achieve sustainable and balanced development.